Antidiabetic Effects of Aloe Vera Whole Leaf Extract and Sitagliptin in Streptozotocin-induced Diabetic Rats - Sobia Javaid; Akbar Waheed (Journal of Rawalpindi Medical College, 2020)
Introduction: Aloe Vera, a perennial herb, is being used since ancient times for the cure of various diseases and is recently being used in curing diabetes due to the synergistic activity of its over 75 biologically active ingredients. The objective of the study was to compare the antidiabetic effects of Aloe Vera whole leaf extract with standard antidiabetic drug Sitagliptin on streptozotocin-induced diabetic rats.